A phase I study of single-agent BEZ235 special delivery system sachet in Japanese patients with advanced solid tumors - Toyoda, Masanori; Watanabe, Koichiro; Amagasaki, Taro; Natsume, Kazuto; Takeuchi, Hiromi; Quadt, Cornelia; Shirao, Kuniaki; Minami, Hironobu (Cancer chemotherapy and pharmacology, 2019)
Purpose BEZ235 is a dual kinase inhibitor of phosphatidylinositol 3-kinase (PI3K) and mammalian target of rapamycin, which are key components of the PI3K pathway. This was an open-label, multicenter, dose-escalation, phase I study of single-agent BEZ235 in Japanese oncology patients to determine the maximum tolerated dose (MTD) of BEZ235 based on dose-limiting toxicities (DLTs). Methods Dose escalation was guided by a standard 3 + 3 method and was based on DLTs observed in Cycle 1 and other safety, pharmacokinetic, and pharmacodynamic information. A total of 35 adult Japanese patients with advanced solid tumors received BEZ235 according to once daily (qd; n = 27) or twice daily (bid; n = 8) dosing schedules. Results Two DLTs, namely, allergic reaction and thrombocytopenia, were observed at 1200 and 1400 mg qd, respectively, while liver dysfunction was reported as a DLT at 400 mg bid. The most common adverse events suspected to be related to BEZ235 in both dosing schedules were diarrhea, nausea, decreased appetite, stomatitis, and thrombocytopenia. Conclusions Although the MTD was not established, the maximum clinically tolerable dose was determined to be 1200 mg because two out of six patients required dose reduction in Cycle 2. The recommended dose was determined to be 1000 mg qd, which was comparable with the results of the first-in-human BEZ235 study in Western patients with advanced solid tumors (NCT00620594). Additionally, the tolerability of BEZ235 400 mg bid in Japanese oncology patients was confirmed in this study. ClinicalTrials.gov identifier NCT01195376.